Performance and economic viability of tambaqui, Colossoma macropomum, selectively bred for weight gain - SILVA,Ana Carla Carvalho (2020)
ABSTRACT Tambaqui, Colossoma macropomum, is one of the most produced species in Brazilian fish farming, which has boosted the development of new technologies to increase its productivity. The aim of this study was to evaluate production performance in two second-generation tambaqui stocks selectively bred for weight gain in a semi-intensive rearing system and assess its influence on total production cost. We analyzed 300 fish (initial mean weight and standard length of 160 g and 17 cm, respectively) of two families (A and B, 150 fish each). The fish were individually marked with microchips and stocked in an 800-m2 excavated pond. For economic analysis, the obtained performance data were extrapolated for a fish farm with a 10-ha pond, adopting the Total Production Cost methodology. After 270 days of farming, the fish from family B were significantly superior (p < 0.05) for all analyzed performance parameters (final weight = 1965.0 g; weight gain = 1786.7 g; biomass gain = 255.2 kg) and morphometric growth in relation to the fish from family A (final weight = 1881.0 g; weight gain = 1737.5 g; biomass gain: 217.7 kg). The total production cost estimations indicated that fish from family B would allow for a 4% reduction in the average fixed cost and a 1% decrease in the total average production cost.